Algoritmo de procesamiento digital de imágenes para la estimación del desbalance antropométrico entre hombros (2020)
In the area of occupational medicine, x-ray examinations are frequently performed to support the diagnosis of anthropometric shoulder imbalance, which is important for the detection of spine-related diseases such as scoliosis. However, continuous exposure to radiation dose is not recommended for the health of individuals. Therefore, alternatives have been proposed for the evaluation of this type of anthropometric imbalance, based on the application of advanced digital image processing techniques that require specialized computer resources and knowledge of advanced mathematics. Therefore, in the present integral work of degree a new non-invasive method is proposed in which a computational algorithm was developed that supports the medical diagnosis from the implementation of basic techniques of digital image processing based on the application of operations of linear algebra in photographs of the frontal plane of the human body to estimate the imbalance between shoulders with a low computational cost. The development of the computational algorithm was implemented in Matlab. The results of this work are compared with those obtained by means of a radiological examination in 5 patients who have the diagnosis of the X-ray examination and with the results provided by a health professional who applied the plumb test to establish the rise and fall of shoulders, that is, in this case there is no numerical value of the imbalance.